CCKAR is a biomarker for prognosis and asynchronous brain metastasis of non-small cell lung cancer - Liang, Nan; Sun, Suohui; Li, Zheng; Wu, Tao; Zhang, Chunpu; Xin, Tao (Frontiers in Oncology, 2023)
Background Non-small cell lung cancer (NSCLC) is the most common histological type of lung cancer, and brain metastasis (BM) is the most lethal complication of NSCLC. The predictive biomarkers and and risk factors of asynchronous BM is still unknown. Materials and Methods A total of 203 NSCLC patients were enrolled into our cohort and followed up. The clinicopathological factors were investigated such as tumor size, T stage, lymphatic invasion, metastasis and asynchronous BM. CCKAR expression in NSCLC and resected BM was assessed by IHC, and CCKAR mRNAs in NSCLC and para-tumor tissues were estimated by qRT-PCR. The correlations between CCKAR expression, BM and other clinicopathological factors were assessed by chi-square test, and prognostic significance of CCKAR was estimated by univariate and multivariate analyses. Results CCKAR was highly expressed in NSCLC tissues compared with para-tumor tissues. CCKAR expression in NSCLC was significantly associated with asynchronous BM. The BM percentages for NSCLC patients with low and high CCKAR were surprisingly 5.2% and 66.6%, respectively. CCKAR expression and BM were unfavorable factors predicting unfavorable outcome of NSCLC. Moreover, CCKAR expression in NSCLC was an independent risk factor of asynchronous BM. Conclusions CCKAR is a prognostic biomarker of NSCLC. CCKAR expression in NSCLC is positively associated with asynchronous BM, and also is a risk factor of asynchronous BM from NSCLC.